Hypnosis in patients with perceived stress - a systematic review - S Fisch; B Brinkhaus; M Teut (BMC, 2017)
Abstract Background Although hypnosis and hypnotherapy have become more popular in recent years, the evidence for hypnosis to influence perceived stress is unclear. In this systematic review we searched and evaluated randomized clinical studies investigating the effect of hypnosis on perceived stress reduction and coping. Methods The Cochrane Central Register of Controlled Trials, the Cochrane Database of Systematic Reviews, the Database of Abstracts of Review of Effects, EMBASE, Medline, PsycINFO, PSYNDEX and PubMed were systematically screened from their inception until December 2015 for randomized controlled trials (RCTs) reporting about hypnosis or hypnotherapy for stress reduction in healthy participants. Risk of Bias was assessed according the Cochrane Collaboration recommendations. Results Nine RCTs with a total of 365 participants met the inclusion criteria and were included in this review. Most included participants were medical students, predominantly female (n = 211). Mean age of participants ranged in most studies between 20 and 25 years, in three studies the mean ages were between 30 and 42 years. Perceived stress was measured by a wide range of psychological questionnaires including Face Valid Stress Test, Stress Thermometer, and immunological data was collected. All nine included studies used explorative designs and showed a high risk of bias. Six out of nine studies reported significant positive effects of hypnosis for stress reduction in the main outcome parameter compared to control groups (3 active controls, 3 no therapy controls). Immunological outcomes were assessed in six studies, the results were inconclusive. Conclusions Due to exploratory designs and high risk of bias, the effectiveness of hypnosis or hypnotherapy in stress reduction remains still unclear. More high quality clinical research is urgently needed.